2004
DOI: 10.1111/j.1365-2362.2004.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RUNX3 protein in human gastric mucosa, intestinal metaplasia and carcinoma

Abstract: These data suggest that RUNX3 may play a physiologic role in chief cells and G cells in gastric mucosa, and that suppression of RUNX3 expression in intestinal metaplasia and carcinoma of human stomach may be implicated in gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 26 publications
0
51
3
Order By: Relevance
“…Specifically, no G-cells in the antral mucosa showed any RUNX3 expression (Figure 3a), despite a recent report that RUNX3 is expressed in a subset of normal gastric epithelial cells, notably in chief cells of fundic glands and in G-cells located in the pyloric portion of the normal stomach (Osaki et al, 2004). Furthermore, we observed nuclear RUNX3 staining in some tumour cells (Table 2, Figure 4b).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Specifically, no G-cells in the antral mucosa showed any RUNX3 expression (Figure 3a), despite a recent report that RUNX3 is expressed in a subset of normal gastric epithelial cells, notably in chief cells of fundic glands and in G-cells located in the pyloric portion of the normal stomach (Osaki et al, 2004). Furthermore, we observed nuclear RUNX3 staining in some tumour cells (Table 2, Figure 4b).…”
Section: Discussioncontrasting
confidence: 46%
“…These observations were linked with the discovery of RUNX3 silencing in about 60% of human gastric cancer specimens analysed (Li et al, 2002). These results led to several studies being published where the loss of RUNX3 appeared as an important event in gastric carcinogenesis (Ito and Miyazono, 2003;Bae and Choi, 2004;Fukamachi and Ito, 2004;Osaki et al, 2004). Brenner et al (2004), on the other hand, reported that, at E4 weeks of age, Runx3 À/À mice (with a heterogeneous ICR and MF1 genetic background) developed colitis and only at an older age (E8 months) went on to develop gastric mucosal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, the role of RUNX3 as a possible gastric tumor suppressor is yet controversial. 7,12,[14][15][16] Moreover, the results of present study are not consistent with those of the previous reports in that the positive MSP expression of the RUNX3 gene was found only in 32.9% of the patients, which is relatively lower than those of the previous reports (45-69%), 7,8 including the Korean-specific data (56-64%). 11,12 RUNX3-specific methylation was more frequently identified in the gastric carcinoma specimens (32.9%) than in the nonneoplastic mucosa (11.4%), although marginally significant (p=0.053).…”
Section: Discussioncontrasting
confidence: 57%
“…12 In addition, methylation of the multiple tumor suppressor genes including RUNX3 were found to increase with age in the nonneoplastic gastric epithelia. 13 Although the absence of RUNX3 expression has been reported in several studies on the human gastric carcinoma, 7,11,12,14,15 a recent study reported that the immunohistochemical staining detected the RUNX3 protein expression in the infiltrating leukocytes, but not in the gastric epithelium. 16 Therefore, the low levels of RUNX3 expression in the gastric epithelium and the absence of downregulation of RUNX3 in the gastric cancer do not support the idea that RUNX3 functions as a gastric tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…A mutation of Arg122 to Cys in the conserved Runt domain abolished the tumor-suppressive effect of RUNX3 (Li et al, 2002). Several other groups have also demonstrated the expression of RUNX3 mRNA and/or protein in gastric epithelial cells (Osaki et al, 2004;Oshimo et al, 2004;Torquati et al, 2004;Wei et al, 2005;Zavros et al, 2005;Katuri et al, 2006;Peng et al, 2006;Usui et al, 2006). However, others have failed to demonstrate the expression of Runx3 in normal gastric epithelial cells immunohistochemically using G-poly and this has led them to question its contribution to carcinogenesis in GIT epithelium (Levanon et al, 2001(Levanon et al, , 2003Brenner et al, 2004, Carvalho et al, 2005.…”
mentioning
confidence: 99%